2018
DOI: 10.1051/itmconf/20182300006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the occurrence of drought in Poland by 2060 based on the HTC index and probability distributions

Abstract: This article attempts to assess the future occurrence of a drought using the Sieljaninova hydrothermal index (HTC). Air temperature and total precipitation were simulated for current conditions (2000) and forecast for eight locations of meteorological stations in Poland according to the HAD and GFDL scenarios for RCP 45 and 60 for 2040 and 2060.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 8 publications
(3 reference statements)
2
11
0
Order By: Relevance
“…Dendrochronological data showed significantly smaller rings having formed during 52.1 % of these. Dobrovolný et al (2015) found very similar results for the Czech Republic based on a set of 3194 oak-ring-width samples for the last 1250 years (761-2010). Negative tree-ringwidth extremes were confirmed in documentary sources in 53 % of cases.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Dendrochronological data showed significantly smaller rings having formed during 52.1 % of these. Dobrovolný et al (2015) found very similar results for the Czech Republic based on a set of 3194 oak-ring-width samples for the last 1250 years (761-2010). Negative tree-ringwidth extremes were confirmed in documentary sources in 53 % of cases.…”
Section: Discussionsupporting
confidence: 53%
“…Using documentary sources, two megadroughts (1540 and 1590) were also qualified as very outstanding droughts in the Czech Republic (Brázdil et al, 2013). Of those, however, only the year 1590 had a negative tree-ring width index (TRW) (of −1.818), although this value was not very high (see Table S1 in the Supplement in Dobrovolný et al, 2015). Brázdil et al (2013) using documentary evidence also distinguished three other outstanding droughts in the Czech Lands (1616, 1718, and 1719).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations